2012
DOI: 10.1111/j.1558-5646.2012.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

PHYLOGENETIC CONSTRAINTS IN KEY FUNCTIONAL TRAITS BEHIND SPECIES’ CLIMATE NICHES: PATTERNS OF DESICCATION AND COLD RESISTANCE ACROSS 95DROSOPHILASPECIES

Abstract: Species distributions are often constrained by climatic tolerances that are ultimately determined by evolutionary history and/or adaptive capacity, but these factors have rarely been partitioned. Here, we experimentally determined two key climatic niche traits (desiccation and cold resistance) for 92-95 Drosophila species and assessed their importance for geographic distributions, while controlling for acclimation, phylogeny, and spatial autocorrelation. Employing an array of phylogenetic analyses, we document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
378
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 279 publications
(392 citation statements)
references
References 57 publications
12
378
2
Order By: Relevance
“…We also observed that many more genes were DE in D. virilis than D. montana. One potential reason for this may be that D. virilis is less cold tolerant than D. montana (Kellermann et al, 2012;Vesala et al, 2012b) and thus the cold acclimation treatment may be more stressful for D. virilis than D. montana, promoting a stronger cold acclimation response. In support of this we also note that the average fold change in genes DE in both species was also slightly larger in D. virilis than D. montana (Figure 1b).…”
Section: Go Term Enrichment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that many more genes were DE in D. virilis than D. montana. One potential reason for this may be that D. virilis is less cold tolerant than D. montana (Kellermann et al, 2012;Vesala et al, 2012b) and thus the cold acclimation treatment may be more stressful for D. virilis than D. montana, promoting a stronger cold acclimation response. In support of this we also note that the average fold change in genes DE in both species was also slightly larger in D. virilis than D. montana (Figure 1b).…”
Section: Go Term Enrichment Analysismentioning
confidence: 99%
“…These species belong to the D. virilis species group, and diverged from each other approximately 9-11 mya (Reis et al, 2008;Morales-Hojas et al, 2011). Both species show a high level of cold tolerance compared to other drosophilids, and D. montana is significantly more cold tolerant than D. virilis (Kellermann et al, 2012;Vesala et al, 2012b). These species have adapted to live in quite different environmental conditions (D. montana is found at high latitudes (30-70°N) and altitudes while D. virilis is a human commensal found at lower latitudes (south from 35°N) (Throckmorton, 1982)) but both exhibit a similar cold acclimation phenotype, whereby flies kept at sub-optimal temperatures show increased cold tolerance as measured by chill-coma recovery time (Vesala et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, flies were reared at 20°C at a 12-h/12-h light/dark cycle and maintained on an oat-based medium (Leeds); some species, however, required the addition of Opuntia cactus and banana to medium. Experimental flies were controlled for larval density and age effects and prepared for trait measurements (20). For each species we examined 10 flies per sex unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…For a more detailed explanation of stocks and experimental methods, see ref. 20. Briefly, flies were reared at 20°C at a 12-h/12-h light/dark cycle and maintained on an oat-based medium (Leeds); some species, however, required the addition of Opuntia cactus and banana to medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation